2002
DOI: 10.1002/1521-3773(20021018)41:20<3800::aid-anie3800>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel, Acentric Metal–Organic Coordination Polymers from Hydrothermal Reactions Involving In Situ Ligand Synthesis

Abstract: The pyridyltetrazolate ligand formed in situ from NaN3 and 3‐cyanopyridine in the presence of ZnCl2 or CdCl2 in water affords acentric (1) or chiral (2) coordination polymers, respectively. The corresponding reaction of ZnCl2 with 4‐cyanopyridine gives acentric 3 (not shown). Compounds 1–3 are second harmonic generation active.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
208
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(214 citation statements)
references
References 2 publications
6
208
0
Order By: Relevance
“…The construction of coordination polymers from preliminarily obtained molecular fragments is one of the important directions in modern chemistry that is actively discussed in terms of self-assembly processes and supramolecular chemistry [1][2][3][4][5][6][7][8][9][10]. There are two most essential types of molecular interactions that are used in constructing extended molecular structures, namely, hydrogen bonds and covalent bonding of cationic and anionic complexes with suitable ligands.…”
mentioning
confidence: 65%
“…The construction of coordination polymers from preliminarily obtained molecular fragments is one of the important directions in modern chemistry that is actively discussed in terms of self-assembly processes and supramolecular chemistry [1][2][3][4][5][6][7][8][9][10]. There are two most essential types of molecular interactions that are used in constructing extended molecular structures, namely, hydrogen bonds and covalent bonding of cationic and anionic complexes with suitable ligands.…”
mentioning
confidence: 65%
“…More recently, Xiong et al [11] reported an in situ formation of 5-substituted 1H-tetrazoles from nitriles and NaN 3 in hydrothermal synthesis of coordination polymers. In this communication, we report the unexpected in situ formation of a substituted tetrazole ligand, 5-(2-pyridyl)-1H-tetrazole (HL), and its Cu(II) and Mn(II) complexes, MnL 2 (H 2 O) 2 (1) and CuL 2 (H 2 O) 2 (2), which contain two-dimensional (2D) hydrogen-bonded networks via interaction between coordinated water molecules and adjacent tetrazole ligands.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14] Although controlling over the packing arrangements of molecules through the employment of rational design principles has taken progress in organic and inorganic-organic hybrid material field, [15][16][17][18][19] crystal engineering does not develop to the stage where a desired structure or crystal symmetry can be ensured. However, some successful examples certified noncentrosymmetric crystals can be reached by introducing chiral compound or interesting hydrogen-bonding interactions.…”
Section: Introductionmentioning
confidence: 99%